The Correlation Between Students’ Reading Habit of Novel And Their Ability in Writing Recount (ELang | An English Language Education Journal, 2018)
This paper entitled The correlation between students’ habit of reading novel and their ability in writing recount text. This paper aimed to know the level of habit in reading novel of the fourth semester of Bale Bandung University in the academic year of 2017, examining their writing ability in recount text, and finding out whether there is correlation between students’ reading habit of novel and their ability in writing recount text. 30 students were taken as the sample of this research through random sampling technique. Researcher used questionnaire to know students’ level of reading habit in reading novel and writing test to measure students’ ability of writing recount text as research instruments. After gave and calculating the instruments, researcher find out the average of the sample have good reading habit and fair ability in writing recount text. Then the result was analyzed by using Pearson Product Moment Correlation method. The calculation showed that the score of r is 0.272. Thus, the r value is between 0.200-0.400 and included into low category. It means that the degree of the correlation is low and positive. The value of t observed is 1.264. The critical value t table is 2.408, as the value of the t observed is smaller than the value of critical t (t-table) 1.264